2014
DOI: 10.3389/fpsyt.2014.00094
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Differences in Planum Temporale in Schizophrenia and Bipolar Disorder Revealed by Statistical Analysis of Labeled Cortical Depth Maps

Abstract: Differences in cortical thickness in the lateral temporal lobe, including the planum temporale (PT), have been reported in MRI studies of schizophrenia (SCZ) and bipolar disorder (BPD) patients. Most of these studies have used a single-valued global or local measure for thickness. However, additional and complementary information can be obtained by generating labeled cortical distance maps (LCDMs), which are distances of labeled gray matter (GM) voxels from the nearest point on the GM/white matter (WM) (inner)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Ratnanather et al. reported that thickness differences of the left planum temporale could differentiate HC, BD and SZ groups. Hatton et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ratnanather et al. reported that thickness differences of the left planum temporale could differentiate HC, BD and SZ groups. Hatton et al.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported cortical thinning of the left paracingulate region (BA 32) [ROI: (42); wholebrain: (34,37,40,41,45)]. Six studies reported cortical thinning of the left superior temporal gyrus (BA 22) [ROI: (32,44); whole-brain: (31,34,37,41)]. Some whole-brain studies also reported more widespread cortical thinning across the temporal lobes [including regions of the temporal pole (BA 38) (34, 37), middle temporal gyrus (BA 21) (34,37), and inferior temporal gyrus (BA 20) (34,37,41)].…”
Section: Cortical Thickness In Bd Compared To the Hc Groupmentioning
confidence: 99%
“…Volumetric reductions of the STG(53) and morphological abnormalities of the planum temporale(54) have long been observed in different phases of the illness, and these same temporal regions have been implicated in the genesis of psychotic symptoms(55). …”
Section: Discussionmentioning
confidence: 99%
“…Based on this tissue segmentation, the cortical thickness was calculated using Labeled Cortical Distance Mapping (LCDM). LCDM is a well-validated, high resolution approach that has successfully been used to characterize difference in cortical thickness in psychopathology including Alzheimerā€™s and schizophrenia (Miller et al, 2003; Ratnanather et al, 2013, 2014; Takayanagi et al, 2013; Wang et al, 2007; Karnik-Henry et al, 2012). The LCDM technique characterizes cortical morphometry in terms of the distribution of labeled distances of GM voxels from the grey matter/white matter (GM/WM) surface (Ceyhan et al, 2011, 2013; Miller et al, 2000; Ratnanather et al, 2001).…”
Section: Methodsmentioning
confidence: 99%